2017
DOI: 10.1515/cclm-2016-1060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cannabinoids concentration and stability in standardized preparations of cannabis tea and cannabis oil by ultra-high performance liquid chromatography tandem mass spectrometry

Abstract: As the first and most important aim of the different cannabis preparations is to guarantee therapeutic continuity in treated individuals, a strictly standardized preparation protocol is necessary to assure the availability of a homogeneous product of defined stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 21 publications
7
94
1
1
Order By: Relevance
“…Complicating matters are the allogamous (variable) and unstable nature of the Cannabis plant and the inherent inconsistencies in the chemical contents across plant batches and derived formulations, which are affected by genetic characteristics, but also environmental, cultivation, and storage conditions (Thomas and Pollard, 2016; Pacifici et al, 2017, 2018). These factors present challenges for both medical cannabis consumers and researchers as patients never have continuous access to cannabis products with precisely consistent chemotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Complicating matters are the allogamous (variable) and unstable nature of the Cannabis plant and the inherent inconsistencies in the chemical contents across plant batches and derived formulations, which are affected by genetic characteristics, but also environmental, cultivation, and storage conditions (Thomas and Pollard, 2016; Pacifici et al, 2017, 2018). These factors present challenges for both medical cannabis consumers and researchers as patients never have continuous access to cannabis products with precisely consistent chemotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that cannabinoids concentrations in oil preparations vary according to temperature and time of extraction, other than highlighting a better stability of cannabinoids in oil extracts rather than in alcohol or in decoction …”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of active ingredients for manufacture of Cannabis -based drugs can be achieved using aqueous (decoction) [39], organic (e.g., ethanolic) [40], supercritical fluid [41, 42] and edible plant oil-based extraction [43] (Fig. 2), with aqueous being the least appropriate given the low solubility of cannabinoids in water [44, 45]. Purification of the botanical drug substance may involve repeated extraction, chromatographic separation, distillation, as well as winterisation, whereby non-target lipid-soluble materials, such as waxes, are removed by filtration at –20°C [46].…”
Section: Cannabis Drug Formsmentioning
confidence: 99%
“…Whilst a large number of analytical techniques have been employed for the quantification of Cannabis botanical raw material [28], including the monograph Cannabis Flos from the Dutch Office of Medicinal Cannabis, limited attention has been given to the quantification of cannabinoids within Cannabis botanical drug substances or CME [27-29, 52]. This is of significant concern given the effects different extraction protocols could have on sample matrices, the chemical composition of active ingredients [27], storage requirements [45, 53] and subsequent quantitative assessment of cannabinoids. The following sub-sections discuss a validation scheme compliant with the ICH Q2 (R1) guideline and highlight generalised validation parameters for the quantification of cannabinoids within CME, with emphasis on potential challenges for fulfilling these criteria.…”
Section: Validation Characteristics For Analytical Proceduresmentioning
confidence: 99%